The Effect of Implementing Project Based Learning Assisted by Manipulative Learning Media on Elementary School Students' Understanding - Maghfirotul Munadhiroh; Risma Elsafitri; Nofa Fibriana; Nur Mulia Ningsih (AJER: Advanced Journal of Education and Religion, 2024)
Project Based Learning is a learning model that is carried out to solve problems by making real projects or products. The purpose of this study was to see how much influence the application of the project-based learning model had on students’ understanding of the triangle material of grade IV elementary school pucangarum 1. This type of reserch is quantitative, quasy Exsperimental reserch type, reserch design nonequivalent control group design. This study consisted of an experimental class and a control class. The instruments used were a student questionnaire, a Pretest, and a Posttest. The data analysis technique uses the N-gain test for the experimental type, the average is 0.69, which is pretty compelling. The project-based learning hypothesis test has an average significance of 84.67, and the conventional learning model has an average of 76.00. Ho is rejected, and ha is accepted, meaning that there is an influence of the project-based learning model on student understanding.